The impact of health insurance on hypertension care: a household fixed effects study in India - Feng, Zixuan; Chen, Qiushi; Jiao, Lirui; Ma, Xuedi; Atun, Rifat; Geldsetzer, Pascal; Bärnighausen, Till; Chen, Simiao (BMC public health, 2024)
Introduction: Hypertension is highly prevalent in India, but the proportion of patients achieving blood pressure control remains low. Efforts have been made to expand health insurance coverage nationwide with the aim of improving overall healthcare access. It is critical to understand the role of health insurance coverage in improving hypertension care. Methods: We used secondary data from the nationally representative sample of adults aged 15–49 years from the 2015–2016 National Family Health Survey (NFHS) in India. We defined the hypertension care cascade as four successive steps of (1) screened, (2) diagnosed, (3) treated, and (4) controlled, and operationalized these variables using blood pressure measurements and self-reports. We employed household fixed effect models that conceptually matched people with and without insurance within the household, to estimate the impact of insurance coverage on the likelihood of reaching each care cascade step, while controlling for a wide range of additional individual-level variables. Results: In all 130,151 included individuals with hypertension, 20.4% reported having health insurance. For the insured hypertensive population, 79.8% (95% Confidence Interval: 79.3%-80.3%) were screened, 49.6% (49.0%-50.2%) diagnosed, 14.3% (13.9%-14.7%) treated, and 7.9% (7.6%-8.2%) controlled, marginally higher than the percentages for the uninsured 79.8% (79.5%-80.0%), 48.2% (47.9%-48.6%), 13.3% (13.1%-13.5%), and 7.5% (7.4%-7.7%) for each cascade step, respectively. From the household fixed effects model, health insurance did not show significant impact on the hypertension care cascade, with the estimated relative risks of health insurance 0.97 (0.93–1.02), 0.97 (0.91–1.03), 0.95 (0.77–1.30), and 0.97 (0.65–1.10) for each cascade step, respectively. We further performed stratified analyses by sociodemographic and behavioral risk factors and a sensitivity analysis with district fixed effects, all of which yielded results that confirmed the robustness of our main findings. Conclusions: Health insurance did not show significant impact on improving hypertension care cascade among young and middle-aged adults with hypertension in India. Innovative strategies for overcoming practical barriers to healthcare services in addition to improving financial access are needed to address the large unmet need for hypertension care.
Gesehen am 06.11.2024